Sampling Palms for Lethal Yellowing and Texas Phoenix Palm Decline Phytoplasmas - Brian Bahder; Ericka Helmick (EDIS, 2018)
In Florida, palms are an economically important group of trees in the nursery and landscaping industries. Phytoplasma diseases of palms are a major concern because they infect a wide variety of these valuable ornamental palms, and they are lethal. Once symptoms appear, trees begin to decline, frequently rapidly, and can die in as few as 3 to 5 months. This 4-page fact sheet written by Brian W. Bahder and Ericka E. Helmick and published by the UF/IFAS Department of Entomology and Nematology describes how to sample palms for disease and how to submit samples to the Vector Entomology Lab. Includes a table listing equipment and supplies and protocol for sampling palm trunk tissue. http://edis.ifas.ufl.edu/in1197